1998
DOI: 10.1046/j.1365-3040.1998.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-induced ethylene biosynthesis and the control of nodulation in alfalfa

Abstract: We previously reported that inhibition of ethylene biosynthesis with aminoethoxyvinylglycine (AVG) eliminated the inhibitory effect of NO 3 -on nodulation of alfalfa (Medicago sativa L. cv. Aragon) plants grown aeroponically. In this work, the effect of Ag + , as an inhibitor of ethylene action, has been studied in plants growing aeroponically or in darkened tubes with vermiculite, and low-nitrate or high-nitrate solution. Vermiculite-grown plants developed up to 3 times as many nodules as did those growing ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 36 publications
(53 reference statements)
2
50
0
1
Order By: Relevance
“…Furthermore, if nitrogen fixation in the bacteroids is impaired by the exceedingly low O 2 levels, the plant which utilizes rhizobial nitrogen fixation as a unique source of nitrogen loses that nitrogen source. It is possible that the nitrate mechanism that is also known to regulate nodulation (Caba et al 1998;Schmidt et al 1999;Ferguson et al 2010) might be deregulated under waterlogging conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if nitrogen fixation in the bacteroids is impaired by the exceedingly low O 2 levels, the plant which utilizes rhizobial nitrogen fixation as a unique source of nitrogen loses that nitrogen source. It is possible that the nitrate mechanism that is also known to regulate nodulation (Caba et al 1998;Schmidt et al 1999;Ferguson et al 2010) might be deregulated under waterlogging conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in nodule mass with Ag + treatment observed here is not well understood. We know, however, that Ag + delays nodule organogenesis (Caba et al, 1998), and that nodules of Ag + -treated plants appeared smaller and more juvenile than the rest at harvest. A similar argument could be presented for the effect of low inoculum dose on nodule mass (Table 5).…”
Section: mentioning
confidence: 95%
“…nigra ; Zaat et al, 1989) and soybean (Sugamuna et al, 1995 ;Ligero et al, 1999). Ethylene inhibitors significantly increased nodulation in alfalfa (Ligero et al, 1991 ;Caba et al, 1998) and in soybean (Ligero et al, 1999), even in the presence of inhibitory levels of nitrate, and restored nodulation in some pea nodulation mutants (Fearn & LaRue, 1991). It has also been suggested that endogenous ethylene provides positional information controlling the site where nodule primordia are formed (Heidstra et al, 1997).…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations